A review on mechanistic understanding of MnO2 in aqueous electrolyte for electrical energy storage systems. (17th August 2020) - Shin, Jaewook; Seo, Joon Kyo; Yaylian, Riley; Huang, An; Meng, Ying Shirley
ABSTRACT: The demand for the large-scale storage system has gained much interest. Among all the criteria for the large-scale electrical energy storage systems (EESSs), low cost ($ k Wh −1 ) is the focus where MnO2 -based electrochemistry can be a competitive candidate. It is notable that MnO2 is one of the few materials that can be employed in various fields of EESSs: alkaline battery, supercapacitor, aqueous rechargeable lithium-ion battery, and metal-air battery. Yet, the technology still has bottlenecks and is short of commercialisation. Discovering key parameters impacting the energy storage and developing systematic characterisation methods for the MnO2 systems can benefit a wide spectrum of energy requirements. In this review, history, mechanism, bottlenecks, and solutions for using MnO2 in the four EESSs are summarised and future directions involving more in-depth mechanism studies are suggested.